MODERN APPROACHES TO TRAINING PERSONNEL IN THE FIELD OF SPORTS - Axmedov Umidjon Usmonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes modern approaches to training personnel in the field of sports.